Comparative Analysis of Dibutyric cAMP and Butyric Acid on the Differentiation of Human Eosinophilic Leukemia EoL-1 Cells - Jung, YunJae (Immune Netw, 2015)
Purification of enough numbers of circulating eosinophils is difficult because eosinophils account for less than 5% peripheral blood leukocytes. Human eosinophilic leukemia EoL-1 cells have been considered an in vitro source of eosinophils as they can differentiate into mature eosinophil-like cells when incubated with dibutyryl cAMP (dbcAMP) or butyric acid. In this study, the viability and phenotypic maturation of EoL-1 cells stimulated by either dbcAMP or butyric acid were comparatively analyzed. After treatment with 100 µM dbcAMP or 0.5 µM butyric acid, EoL-1 cells showed morphological signs of differentiation, although the number of nonviable EoL-1 cells was significantly increased following butyric acid treatment. Stimulation of EoL-1 cells with 0.5 µM butyric acid more effectively induced the expression of mature eosinophil markers than stimulation with dbcAMP. These results suggest that treatment of EoL-1 cells with 0.5 µM butyric acid for limited duration could be an effective strategy for inducing their differentiation. Considering that expression of CCR3 was not sufficient in EoL-1 cells stimulated with 0.5 µM butyric acid, treatment of the chemically stimulated EoL-1 cells with cytokines, which primarily support eosinophil maturation, would help to obtain differentiated EoL-1 cells with greater functional maturity.